2021
DOI: 10.3390/plants10061095
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Hydrogen Maintains the Storage Quality of Chinese Chive through Improving Antioxidant Capacity

Abstract: Chinese chive usually becomes decayed after a short storage time, which was closely observed with the redox imbalance. To cope with this practical problem, in this report, molecular hydrogen (H2) was used to evaluate its influence in maintaining storage quality of Chinese chive, and the changes in antioxidant capacity were also analyzed. Chives were treated with 1%, 2%, or 3% H2, and with air as the control, and then were stored at 4 ± 1 °C. We observed that, compared with other treatment groups, the applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…For above cases, H 2 might be integrated with other downstream gasotransmitters, including nitric oxide and hydrogen sulfide, as well as regulating some phytohormones [11,16]. In terms of postharvest storage period, previous results also revealed that H 2 could prolong the shelf life of some vegetables, fruits, and flowers, including kiwifruit [17] and daylily bud [18], as well as lisianthus [19], carnation [20], and Chinese chive [21] when hydrogen-rich water, H 2 fumigation, or magnesium hydride (a H 2 -releasing material) were separately applied. Since there were numerous functions of H 2 observed in the vegetative growth stage and postharvest period, it is reasonable to deduce that molecular hydrogen might have significant influence in reproductive growth and seed developmental stages, both of which are very important for crop production, especially for rice.…”
Section: Introductionmentioning
confidence: 99%
“…For above cases, H 2 might be integrated with other downstream gasotransmitters, including nitric oxide and hydrogen sulfide, as well as regulating some phytohormones [11,16]. In terms of postharvest storage period, previous results also revealed that H 2 could prolong the shelf life of some vegetables, fruits, and flowers, including kiwifruit [17] and daylily bud [18], as well as lisianthus [19], carnation [20], and Chinese chive [21] when hydrogen-rich water, H 2 fumigation, or magnesium hydride (a H 2 -releasing material) were separately applied. Since there were numerous functions of H 2 observed in the vegetative growth stage and postharvest period, it is reasonable to deduce that molecular hydrogen might have significant influence in reproductive growth and seed developmental stages, both of which are very important for crop production, especially for rice.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have been observed that H 2 -modified atmosphere can also prolong the shelf life of vegetables and fruits. For example, a ~1.2 × 10 3 µM H 2 fumigation can maintain the postharvest quality of Chinese chive at 4 • C [21]. In kiwifruit, the positive effect of ~0.2 µM H 2 gas on prolonging shelf life was similar with that of 1-MCP (0.04 µM) [22].…”
Section: The Effective Concentration Range Of H 2 Treatmentmentioning
confidence: 89%
“…Pretreatment with HRW by soaking fruits (such as kiwifruit [17], tomato [47], and lychee [18] as well as fresh-cut kiwifruit [48]) for less than 30 min can significantly maintain storage quality and prolong shelf life. H 2 fumigation for pretreatment or throughout storage period can achieve similar effects in kiwifruit [22] (Figure 1) and Chinese chive [21].…”
Section: The Timing Of Application And/or Growth Stagesmentioning
confidence: 91%
See 2 more Smart Citations